Fantastic Four : it's slobberin' time! - Parker, Jeff (Fantastic Four series, 2007)
Mr. Fantastic, Invisible Woman, the Human Torch, and the Thing become unwilling passengers in a hop through space after Mr. Fantastic's attempts to use his Cross-Frequency Modulator to control the villain Street, draws a giant dog from outer space.